A mechanistic model for the prediction of flow pattern transitions during separation of liquid-liquid pipe flows. (October 2022) - Evripidou, Nikola; Avila, Carlos; Angeli, Panagiota
Highlights: A mechanistic model for the prediction of flow pattern transitions in two-phase, oil-water dispersed pipe flows was developed. Mechanistic model can predict the separation of both oil-in-water and water-in-oil dispersions. Dispersion separation is controlled by either the drop settling rate or the coalescence rate. Abstract: A one-dimensional mechanistic model that predicts the flow pattern transitions during the separation of dispersed liquid-liquid flows in horizontal pipes was developed. The model is able to capture the evolution along the pipe of the four characteristic layers that develop from initially dispersed flows of either oil-in-water or water-in-oil at a range of mixture velocities: a pure water layer at the bottom, a settling (flotation/sedimentation) layer, a dense-packed zone, and a pure oil layer on the top. Coalescence correlations from literature were included in the model to predict the drop growth due to binary drop coalescence and the coalescence rate of drops with their corresponding interface. The model predictions on the evolution of the heights of the different layers were partly compared against available experimental data obtained in a pilot scale two-phase flow facility in a test section of 0.037 m inner diameter using tap water and an oil of density 828 kg m −3 and viscosity 5.5 mPa s as test fluids, and in a 0.1 m inner diameter test section using water and an oil of density 857 kg m −3 and viscosity 13.6 mPa s. It was shown that the evolution of the four characteristic layers depends on the rates of drop settling and drop-interface coalescence. Oil-in-water dispersions separated faster than water-in-oil ones, while dispersions with smaller drop-sizes were more likely to exhibit depletion of the dense-packed zone.